Immersive Quiet Rooms for Children with ADHD: Color, Geometry, and Gaze Based Simulation - Nanda Supriyono; Popi Puspitasari (Green Publisher Indonesia, 2026)
Attention-deficit/hyperactivity disorder (ADHD) is a neurodevelopmental condition characterized by difficulties in maintaining attention, regulating sensory responses, and managing behavioral impulses. Environmental design has increasingly been recognized as a supportive intervention that can influence emotional regulation and cognitive performance among children with ADHD. This study explores the design of immersive quiet rooms through the integration of color, geometric elements, and gaze-based simulation to create a calming and adaptive environment for children with ADHD. The research employs a design simulation approach by examining how spatial configurations, visual stimuli, and interactive environmental features affect children’s attention patterns and sensory experiences. A virtual immersive environment was developed to evaluate the impact of different color schemes, geometric compositions, and visual focal points using gaze-based interaction analysis. The findings indicate that carefully selected soft color palettes, balanced geometric patterns, and controlled visual stimuli contribute to improved sensory comfort and reduced visual distraction. The gaze-based simulation demonstrates that specific spatial arrangements and visual elements can guide attention toward calming areas while minimizing overstimulation. This study highlights the potential of immersive quiet rooms as an evidence-based environmental strategy to support children with ADHD by integrating architectural design principles with digital simulation technologies. The proposed approach provides new insights into designing therapeutic learning and relaxation spaces that are responsive to children’s sensory needs and cognitive characteristics.